The Role of Accounting Information Systems in Company Operational Efficiency: A Bibliometric Study - Judijanto, Loso (West Science Accounting and Finance, 2025)
This study explores the role of Accounting Information Systems (AIS) in enhancing company operational efficiency through a bibliometric analysis of academic literature published between 2000 and 2024. Using data retrieved from the Scopus database and analyzed with VOSviewer software, the study maps key research trends, influential authors, and thematic developments in the field. The results reveal that AIS remains a central focus in accounting and information systems research, particularly in areas such as financial control, information use, and managerial decision-making. Recent trends indicate a growing interest in the integration of emerging technologies—such as artificial intelligence, big data analytics, blockchain, and cloud computing—highlighting a shift toward digital transformation and intelligent systems. Co-authorship and country collaboration analyses show active global participation, with strong contributions from the United States, Indonesia, China, and Middle Eastern countries. This study offers valuable insights into the intellectual structure of AIS research, identifies gaps for future inquiry, and underscores the strategic importance of AIS in achieving operational excellence.